Shipping Safety Performance Models on Solid Shipping Lanes: An Internal and Environmental Factors Perspective - Kuncowati, Kuncowati; Teguh Wiyono , S; Tamam, Rycky Badrut (Maritime Park: Journal of Maritime Technology and Society, 2025)
The global shipping lane for international trade in logistics and maritime is a shipping lane that has a high traffic density. Shipping on congested shipping lanes has great potential for the risk of ship damage. To improve shipping safety on dense shipping lanes, the purpose of this study is to analyze the relationship between ship's internal factors and shipping safety performance on dense shipping lanes, analyze the relationship between environmental factors and shipping safety performance on dense shipping lanes and obtain a model of shipping safety performance on dense shipping lanes. The method chosen to achieve the objectives of this study is a quantitative method with the Structural Equation Model (SEM) analysis technique with Smart PLS. The data of this research was obtained from the answers to a questionnaire that will be distributed to the crew of Indonesian-flagged commercial ships that have travelled through dense shipping routes, with a total of 150 crew members. The novelty of the research is a model of shipping safety performance in dense shipping lanes from the perspective of internal and environmental factors. The model shows the relationship of internal ship factors to shipping safety performance on dense shipping lanes by 30.9% and environmental influences on shipping safety on dense shipping lanes by 14.5%.